أسباب الاحتمالات الإعرابية في تفسير البيضاوي: سورتي البقرة وآل عمران أنموذجا - Khalid Nasser Almaliki; Mohamad Hussin; Mat Taib Pa (USIM Press, 2024)
Journal of Islamic Social Sciences and Humanities (Al-'Abqari) Volume 29 No 1 Page (14-38)